Rooming-in Reduces Salivary Cortisol Level of Newborn - Giuseppe De Bernardo; Marina Riccitelli; Maurizio Giordano; Fabrizio Proietti; Desiree Sordino; Mariangela Longini; Giuseppe Buonocore; Serafina Perrone (Hindawi Limited, 2018)
Background. Rooming-in practice improves breastfeeding and reduces newborn stress reactivity. When this modality is not available, partial rooming-in after birth can be considered. Salivary cortisol levels (SCLs) are considered reliable biomarkers to indicate stress. Objective. To test the hypothesis that rooming-in duration impacts neonatal stress response in hospitalized newborns. Design/methods. Forty term newborns, enrolled in the Neonatology and Obstetrics Nursing, C.G. Ruesch, Naples, Italy, were divided, according to the mother's choice, into the study (SG; n=20) and control (CG; n=20) groups if they received full (24 hs) or partial (14 hs) rooming-in care, respectively. Saliva samples were collected from all babies between 7:00 a.m. and 8:00 a.m. of the 3rd day of life by using oral swab. Salivary cortisol levels were measured using an enzyme immunoassay kit (Salimetrics LLC, PA, USA). Results. A statistically significant difference in the SCLs between SG and CG was found (median: 258 ng/dl versus 488.5 ng/dl; p=0.048). Conclusions. Data support the practice of full rooming-in care compared with partial rooming-in. The rooming-in duration clearly reduces SCLs and likely neonatal stress. These lower SCLs may have long-term positive effects reducing the risk of metabolic syndrome, high blood pressure, and cognitive and behavioural changes.